Choices and Reasons for RSGM Baiturrahmah Co-ass Student Batch 2018 in Continuing Specialization - Adni Muswita; Sri Pandu Utami (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Background: The dentistry profession continuously presents information aimed at improving its discipline consistently and measurably to improve the oral health of patients. Specializes in any field that is known to be associated with higher productivity. The same is true for the health sector in general and specifically for dentistry where general practice is being matched by the search for demand for specialists. Purpose: This study aims to look at students' choices and reasons for pursuing a dental specialist at RSGM Baiturrahmah. Methods: This is a descriptive study consisting of 71 college students at RSGM Baiturrahmah. Subjects and methods: consisting of students filling out a questionnaire containing 4 questions, the research time was in October 2020 using a questionnaire. Statistical Analysis: The data analysis in this study used the SPSS program with descriptive analysis. Results: showed that the specialist that students were interested in was periodontics as much as 22.22% and the reasons for students to continue to specialize at most were having skills/talents in specialists as much as 38.03%.